How Workload and Work Stress Influence Employee Turnover Intention in Healthcare Settings - Hardityo Hardityo; Tutik Winarsih (Transpublika Publisher, 2025)
There is a rise in employee turnover at healthcare organizations, particularly at Ikhsan Medika Clinic Klaten where the turnover rate is 15%, higher than the industry average. The main reasons for this turnover seem to be heavy workloads and stress from clinical environments. This research looks into how the workload and stress at work impact employee turnover intentions at the Ikhsan Medika Clinic in Klaten. This particular study falls under the category of quantitative research. A total of 35 participants were selected by probability sampling. To gather data, a questionnaire was utilised. Various analytical techniques were employed including instrument validity tests, classical assumption testing, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination analysis. The data was processed using SPSS version 26. After conducting the t-test, it was found that the workload variable showed a t-value of 3.275 with a significance level (sig) of 2.037 < 0.05. This points to a correlation between workload and turnover intentions among employees at the Ikhsan Medika Clinic in Klaten. The research found nothing significant came from work stress towards turnover intention at Ikhsan Medika Clinic, with a t-value of 0.507 and significance level of 2.037. However, workload and work stress were found to influence turnover intention, confirmed by an F-test with a significant value of 9.873 (p < 0.05). The adjusted R-square of 0.618 shows that 38.2% of turnover intention is explained by these factors, whilst 62.8% was determined by factors outside the scope of this analysis.